Impact on Clinical Outcome of Premature Interruption of Cryoenergy Delivery Due to Phrenic Nerve Palsy During Second Generation Cryoballoon Ablation for Paroxysmal Atrial Fibrillation. (8th July 2015) - CHIERCHIA, GIAN‐BATTISTA; MUGNAI, GIACOMO; HUNUK, BURAK; STRÖKER, ERWIN; VELAGIĆ, VEDRAN; SAITOH, YUKIO; IRFAN, GHAZALA; HACIOGLU, EBRU; CICONTE, GIUSEPPE; BRUGADA, PEDRO; DE ASMUNDIS, CARLO
Cryoenergy Interruption Due to Phrenic Nerve Palsy Introduction Right phrenic nerve paralysis (PNP) is the most frequently observed complication occurring during cryoballoon ablation (CB). Our aim was to analyze the impact of the premature interruption (PI) of cryoenergy delivery in a large series of consecutive patients during ablation in the right‐sided veins on clinical outcome. Methods and Results All consecutive patients having undergone second‐generation CB ablation for paroxysmal atrial fibrillation (AF) from July 2012 to September 2014 were included in our analysis. Exclusion criteria were persistent AF, presence of an intracavitary thrombus, uncontrolled heart failure, moderate or severe valvular disease, left atrium (LA) diameter ≥55 mm, and contraindications to general anesthesia. A total 287 consecutive patients with drug‐resistant paroxysmal AF having undergone pulmonary vein isolation by means of CB technology (male 65%, age 57.6 ± 13.1 years) were included. The incidence of PNP in the study population was 8.0% (23/287). At a mean follow‐up of 11.5 ± 3.9 months, the success rate without antiarrhythmic therapy was 81.6%. Patients with PNP had similar rates of AF recurrence compared with those without PNP (17.4% vs. 17.8%; P = 0.9); the former had a mean follow‐up of 10.9 ± 3.7 months, the latter 11.8 ± 4.5 months (P = 0.3). Conclusion Conclusion: Our findings show that patients in whom freezing was interrupted due to PNP had a similar outcome on 1‐year follow‐up compared with those in whom freezing cycles were completed in the septal veins. No baseline clinical or procedural characteristics were found to predict AF recurrence in patients having experienced PNP.